Oestrus synchronization and artificial insemination in kids 8-9 months old - ΚΑΡΑΤΖΑΣ Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In 37 Kids from a block of 82 kids 8-9 months old oestrus synchronization was induced during the breeding season with intravaginal sponges (CRONOLONE) and PMSG injection. After the removal of sponges two inseminations with frozen semen (in plastic tubes of o.5 ml) at 36 hrs and 60 hrs had applied. The number of spermatozoa per tube was 200-250 χ IO6. The conception rate in sychronized and inseminated animals was 62,5%. The litter size increased by 0,56 (P> 0.001). Relationship between the litter size and the live night of animals has not noticed. It is concluded that the age of kids 8-9 months in Greek conditions is suitable for oestrus synchronization with a result of satisfactory conception rate and litter size.